Minimal architectures for landscape – The module as a tool for sustainability - Jorge Garcia Valldecabres; Daniela Besana (Agathón)
The theme of environmental emergency is now at the forefront of discussions on how to plan and conceive architectural design. This paper argues for the opportunity to interpret building design as a circular process that can, at all stages, help designers find conscious and functional answers to the issue of the environmental impact of construction: this calls for a necessary review of the project’s performance requirements, which can find a possible complete and adequate answer in minimal modular architectures. It is indeed believed that the module in architecture can be designed, given the same basic minimum element, as flexible with respect to usage requirements, contexts and achievable performance. To demonstrate the above, research experiences regarding this architectural-design concept are provided.